Home Hospital Care through Telehealth during COVID-19 Pandemic in Nepal - Devkota, Ashok; Pandey, Sagar; Pandey, Yadav; Neupane, Hari; Basnet, Anjan Kumar; Shah, Anish; Thakur, Rahul; Sah, Sumit; Chaudhary, Durgesh; Mahato, Aakash; et al. (Europasian Journal of Medical Sciences, 2022)
COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 has been occurring in waves due to emergence of different strains. During second wave of COVID pandemic in Nepal, largely caused by Delta variant, due to rapid rise in cases, existing hospitals and health facilities were overwhelmed. As a result, telemedicine was expanded to help reduce strain on the healthcare system and meet unusually high demands. A team of physicians with the support from the local government provided hospital level care for patients at home in rural district of Dang in Nepal. This research analyzes implementation of this model of care and outcomes based on review of patient records and treatment guidelines. Within a month, from May 5 to June 13, 2021, a total of 102 patients received care at home. While most patients had mild to moderate disease, 12.8% of patients had severe disease. Telemedicine usage was highest among the 40-59 years age group, with overall recovery rate of 85.3%. The patient satisfaction survey revealed that majority, 86.5% were happy with the medical care they received. This home hospital care model has shown excellent clinical outcomes and high patient satisfaction even in resource limited setting.